HBR's 10 must reads on leadership. (HBR's 10 must reads (Series), 2011)
"Go from being a good manager to being an extraordinary leader. If you read nothing else on leadership, read these 10 articles. We've combed through hundreds of Harvard Business Review articles on leadership and selected the most important ones to help you maximize your own and your organization's performance. This book will inspire you to: motivate others to excel; build your team's self-confidence; provoke positive change; set direction; encourage smart risk-taking; manage with tough empathy; credit others for your success; increase self-awareness; draw strength from adversity"--Page 4 of cover.